Impact of non-verbal communication on collaboration in 3D virtual worlds: case study research in learning of aircraft maintenance practices - Silva, Gustavo (2017)
iLRN 2017. Conferência internacional realizada em Coimbra, Portugal, de 26–29 de junho de 2017.